2012
DOI: 10.2139/ssrn.2049336
|View full text |Cite
|
Sign up to set email alerts
|

The Formal/Informal Employment Earnings Gap: Evidence from Turkey

Abstract: In this study, we examine the formal/informal sector earnings differentials in the Turkish labor market using detailed econometric methodologies and a novel panel data set drawn from the 2006-2009 Income and Living Conditions Survey (SILC). In particular, we test if there is evidence of traditional segmented labor markets theory which postulates that informal workers are typically subject to lower remuneration than similar workers in the formal sector. Estimation of standard Mincer earnings equations at the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
2
15
0
6
Order By: Relevance
“…Tansel (, ), Savasan and Schneider (), Taymaz (), Tansel and Kan (, ), Acar and Tansel (), and Balkan and Tümen () are among the examples.…”
mentioning
confidence: 99%
“…Tansel (, ), Savasan and Schneider (), Taymaz (), Tansel and Kan (, ), Acar and Tansel (), and Balkan and Tümen () are among the examples.…”
mentioning
confidence: 99%
“…The results indicate the static nature of the labor market in Turkey except for the transitions from unemployment. Tansel and Kan (2012b) addressed the formal/informal wage gap in the Turkish labor market. Finally, Kan and Tansel (2012c) studied the definition and the measurement of the informal sector in Turkey and found that lack of social security coverage is the most appropriate way to define informality.…”
mentioning
confidence: 99%
“…Rares sont pourtant les études qui ont exploré les dimensions multiples des divers arrangements contractuels observés dans les faits. Tansel et Kan (2012) ont étudié les écarts salariaux selon que l'emploi est formel ou informel et salarié ou indépendant, tandis que Mocan et Tekin (2003) se sont concentrés sur les différences entre plein temps et temps partiel et entre secteur à but lucratif et secteur à but non lucratif. Ces approches n'ont pas encore été appliquées aux écarts salariaux dans le travail domestique, qui se caractérise par une forte fréquence des emplois informels et flexibles.…”
Section: Caractéristiques Non Monétaires Et éCarts De Salaireunclassified